The RJ Style: Brought to you by Bangladeshi FM radio (Stamford Journal of English, 2013)
In recent years, the popularity of FM Radio stations has brought a unique change in speech style among the Bangladeshi youth. This paper compares the views of both the Radio Jockeys (RJ) and the young listeners to find out to what extent this phenomenon of RJ Speech influences the speech of the youth. The authors of the paper have selected 110 tertiary students randomly to collect their opinions through a questionnaire. Besides, seven RJs of four radio stations were interviewed and recordings of different programmes of the four FM radio stations were analysed to trace the new slang words and pronunciations used in this new style of speaking. The findings show that the young listeners think that they use this style both consciously and unconsciously. They sometimes take up this obviously made up accent to become a part of the popular and stylish group of friends on campus. On the other hand, the RJs do not want to admit that they are adversely influencing standard Bangla. They claim that it is up to the listeners to take the good or bad part of a programme and RJs will always adhere to their unique style. Stamford Journal of English; Volume 6; Page 1-26 DOI: http://dx.doi.org/10.3329/sje.v6i0.13899